RETHINKING Science Communication Education and Training: Towards a Competence Model for Science Communication - Fähnrich, Birte; Wilkinson, Clare; Weitkamp, Emma; Heintz, Laura; Ridgway, Andy; Milani, Elena (Frontiers in Communication, 2021)
Science communication is at a pivotal stage in its development due to the emergence of digital communication platforms that are not only presenting new opportunities but are also leading to new challenges. In this context, science communicators, which can include scientists, researchers, curators, journalists and other types of content producer, may require new types of preparation and support to engage with multiple audiences, across multiple channels. Despite the increasing need for adequate science communication training, research in the field is sparse and oftentimes refers to single case studies, calling for more comprehensive perspectives on what is needed and what is offered to equip future science communicators with relevant competences to cope with the changing science communication ecosystem. Against this backdrop, this paper, which draws on data from RETHINK, a European project comprising seven countries, Italy, the Netherlands, Poland, Portugal, Serbia, Sweden and the UK, takes two approaches. First, we report on findings from a questionnaire survey completed by 459 science communicators across the seven countries, focusing on how science communicators develop their communication skills, the types of training they have received and the types of training they would like to undertake. Second, we assess exploratory data collected from 13 different science communication degree programs regarding how they seek to embed and consider issues of digital transformation within their curricula. On the basis of both analyses, we will introduce ideas for a competence framework that addresses not only working knowledge and skills but also professional (self-)reflection and the overall mindset and worldviews of students, whilst offering capacity for increased consideration of the role of digital transformation.